Cardiopulmonary bypass for resection of low tracheal haemangioma. Issue 6 (June 1990) - Franks, R; Rothera, M
Abstract : A 3 month old girl, weighing 4000 g, presented with a capillary haemangioma obstructing the lower trachea and left main bronchus; it was not responsive to steroids. Using cardiopulmonary bypass to maintain oxygenation the tumour was excised. We are not aware that this technique has been used before for the resection of such an obstructive haemangioma.